Harmony of Multicultural Community Interaction - Hilda Yani (International Journal on Social Science, Economics and Art, 2019)
Diversity is one of the main realities that people experience in the past, present, and future. Diversity can simply be understood as a recognition that a society is diverse and plural. Diversity can bring great benefits, but it can be a trigger for conflict that can be detrimental to the community if not managed properly. To maintain the harmony of relationships in diverse communities, efforts are needed to cultivate awareness of tolerance, the principle of equality, and view differences as God's grace. Cultural awareness with all diversity and potential conflicts in society that leads to the division of diversity is a condition in society where there are differences in various fields, especially ethnicity, race, religion, ideology and culture. Diversity in society is a situation that shows a considerable difference of sorts or types in society.